Macro-financial interactions in a changing world - Eddie Gerba; Danilo Leiva-Leon (Danmarks Nationalbank, 2020)
We measure the time-varying strength of macrofinancial linkages within and across the US and euro area economies by relying on factor models with drifting parameters, where real and financial cycles are extracted and shocks are identified via sign and exclusion restrictions. The main results show that the euro area is disproportionately more sensitive to shocks in the US macroeconomy and financial sector, resulting in an asymmetric cross-border spillover pattern between the two economies. Moreover, while macro-financial interactions have steadily increased in the euro area since the late 1980s, they have oscillated in the US,, exhibiting very long cycles of macro- financial interdependence.
Keywords: E44; C32; C55; F44; E32; F41; 330; Macro-financial linkages; dynamic factor models; TVP-VAR